1999
DOI: 10.1021/bi991755p
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Human Nucleotide Excision Repair Protein XPA with DNA and RPA70ΔC327:  Chemical Shift Mapping and 15N NMR Relaxation Studies

Abstract: Human XPA is an essential component in the multienzyme nucleotide excision repair (NER) pathway. The solution structure of the minimal DNA binding domain of XPA (XPA-MBD: M98-F219) was recently determined [Buchko et al. (1998) Nucleic Acids Res. 26, 2779-2788, Ikegami et al. (1998) Nat. Struct. Biol. 5, 701-706] and shown to consist of a compact zinc-binding core and a loop-rich C-terminal subdomain connected by a linker sequence. Here, the solution structure of XPA-MBD was further refined using an entirely ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 61 publications
6
71
1
Order By: Relevance
“…However, the earlier finding, obtained by chemical shift mapping, which showed that RPA70(1-326) made contact with both the zinc-containing and C-terminal subdomains (41), is consistent with the results of this study. RPA70 and DNA were shown to share a binding surface in the C-terminal subdomain (41). Using direct cross-linking experiments, RPA70 and XPA were found to be positioned in close proximity to the damage site (42).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the earlier finding, obtained by chemical shift mapping, which showed that RPA70(1-326) made contact with both the zinc-containing and C-terminal subdomains (41), is consistent with the results of this study. RPA70 and DNA were shown to share a binding surface in the C-terminal subdomain (41). Using direct cross-linking experiments, RPA70 and XPA were found to be positioned in close proximity to the damage site (42).…”
Section: Discussionsupporting
confidence: 93%
“…These results are not consistent with our previous study using RPA70(181-422) (34). However, the earlier finding, obtained by chemical shift mapping, which showed that RPA70(1-326) made contact with both the zinc-containing and C-terminal subdomains (41), is consistent with the results of this study. RPA70 and DNA were shown to share a binding surface in the C-terminal subdomain (41).…”
Section: Discussioncontrasting
confidence: 58%
“…XPA is one of the damage recognition proteins involved in mammalian NER. The NMR structure of its DNA binding domain is known [49,50] and has recently been subjected to mutagenesis [51]. By monitoring luciferase expression following UV host cell reactivation in XPA deficient cells, the investigators assessed how various XPA DNA binding site mutants could initiate repair.…”
Section: Discussionmentioning
confidence: 99%
“…The "damaged" DNA oligonucleotide, F 26 50, consisted of a 50-mer with a centrally located fluorescein adduct thymine (FldT). The F 26 50 sequence was: 5′-GAC TAC GTA CTG TTA CGG CTC CAT C (FldT)C TAC CGC AAT CAG GCC AGA TCT GC-3′.…”
Section: Dna Substratesmentioning
confidence: 99%
See 1 more Smart Citation